1980
DOI: 10.1073/pnas.77.6.3322
|View full text |Cite
|
Sign up to set email alerts
|

Replication of duplex DNA of phage phi X174 reconstituted with purified enzymes.

Abstract: Replication of the covalently closed duplex replicative form (RF) of phage gX174 DNA has been achieved by couplin two known enzyme systems: (i) synthesis of viral strand circles (SS) from RF, and (if) conversion of SS to nearly complete RF (RF II. In this coupled system, activated RF (gene A-RF II complex) was a more efficient template and generated as many as 10 RF II molecules per RF input, at a rate commensurate with SS synthesis. The (12,13). One system (RF --SS) requires the participation of OX-encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…), containing the (bX174 origin of replication cloned in between the HindIII and BamHI sites of pBR322. This allowed the synthesis of single-stranded probe DNA (Arai et al 1980), which was performed by the incubation of supercoiled plasmid DNA with gene A protein, rep and ssb proteins, and DNA polymerase III holoenzyme (all generously provided by the A. Kornberg laboratory) in a reaction containing 20 mM Tris-C1 (pH 7.5), 80 ~g/ml BSA, 4% glycerol, 20 mM DTT, 1 mM ATP, 16 mM concentrations of the three unlabeled deoxynucleotides and 1.6 mM concentrations of the labeled deoxynucleotide for 1 hr at 30°C. EDTA was then added to 20 mM, SDS to 0.1%, and proteinase K to 50 ~tg/ml.…”
Section: Southern and Northern Blot Analysismentioning
confidence: 99%
“…), containing the (bX174 origin of replication cloned in between the HindIII and BamHI sites of pBR322. This allowed the synthesis of single-stranded probe DNA (Arai et al 1980), which was performed by the incubation of supercoiled plasmid DNA with gene A protein, rep and ssb proteins, and DNA polymerase III holoenzyme (all generously provided by the A. Kornberg laboratory) in a reaction containing 20 mM Tris-C1 (pH 7.5), 80 ~g/ml BSA, 4% glycerol, 20 mM DTT, 1 mM ATP, 16 mM concentrations of the three unlabeled deoxynucleotides and 1.6 mM concentrations of the labeled deoxynucleotide for 1 hr at 30°C. EDTA was then added to 20 mM, SDS to 0.1%, and proteinase K to 50 ~tg/ml.…”
Section: Southern and Northern Blot Analysismentioning
confidence: 99%
“…Primosome-associated ~X RFI or ~,X RFIV DNA is a much better substrate for cleavage with gene A protein than superhelical RFI DNA, as shown by the 20-fold enhancement of the initial rate of DNA synthesis [35]. Besides facilitation of the RF DNA nicking by gene A protein, the primosome may also serve as a helicase during RF DNA replication and may initiate in the replication fork priming of complementary strand synthesis [24,58,59[. Conservation of the primosome on the RF molecule containing the original complementary strand, and thereby favouring its replication within the cell, may explain the dominant role of the genotype of the parental complementary strand in the production of progeny virus [75,76].…”
Section: Ivc Complementary Strand Synthesis During Rf Dna Replicationmentioning
confidence: 99%
“…The question whether complementary strand synthesis starts on the tail of the rolling circle or whether the synthesis is initiated on the segregated circular viral strand is not completely solved. In vitro studies in the ~X system during stage I replication have shown that once assembled on the viral strand, the primosome which is responsible for the initiation of complementary strand synthesis remains bound after the circle has become a covalently closed, supercoiled duplex [24,35,58,59]. Primosome-associated ~X RFI or ~,X RFIV DNA is a much better substrate for cleavage with gene A protein than superhelical RFI DNA, as shown by the 20-fold enhancement of the initial rate of DNA synthesis [35].…”
Section: Ivc Complementary Strand Synthesis During Rf Dna Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…An apparent requirement for localized single-strandedness at the gene A cleavage site (13,14), facilitated by superhelicity, has implicated gyrase in this process (15). Growth of the nascent viral strand ;provides the template for initiation of a complementary strand by primosome action of a ssDNA --RF system identical to that used to initiate synthesis of the parental RF (16).…”
mentioning
confidence: 99%